Caregiver-informed meta-synthesis of caregivers’ experiences with tracheostomy decision-making in pediatrics - Ofosu, Daniel; Scott, Sela; Kammerer, Elise; Lecona, Larissa; Gibson, Kristen; Nitschke, Stephanie; Thompson-Kai, Pam; Chiarieri-Hirsch, Dacia; Qureshi, Nadia; Soril, Lesley; van Manen, Michael; Castro-Codesal, Maria (Frontiers in Pediatrics, 2025)
IntroductionFamily-caregivers facing the decision of a tracheostomy for their child must consider many factors beyond the medical procedure itself, such as quality of life, personal values, and overall care goals.ObjectiveThis study aimed to synthesize the available qualitative literature exploring family-caregivers’ experiences regarding decision-making about tracheostomy for children.MethodsWe conducted a systematic review and meta-synthesis of qualitative studies exploring family-caregivers’ experiences with tracheostomy decision-making for their children. Four parents with lived experience of having to make decisions about tracheostomy for their child were co-investigators for this work. An experienced librarian developed search strategies to systematically search databases for eligible studies. Two researchers independently screened, extracted and conducted thematic analyses of all the included studies. Researchers and parent partners discussed the identified themes, conceptualized them into categories and crafted a coherent narrative that was larger than the individual contributions of each study.ResultsSeventeen studies were included in the meta-synthesis. Our analysis generated seven themes: (1) the initial reaction; (2) what's going to happen to my child; (3) a place for hope; (4) taking on a new role; (5) how are we going to pay the bills; (6) navigating changing relationships; and (7) a new normal: adjusting to life at home. The identified themes indicated that family-caregivers often consider not only the immediate need to extend their child's life during decision-making but also the long-lasting implications for their child's future, their own roles as caregivers, and the impact on their family as a whole.ConclusionThe qualitative literature provides valuable insights into the multifaceted challenges faced by family-caregivers during decision-making and the critical role of healthcare professionals in supporting families through this journey beyond the initial decision.